Prognostic role of plasma vitamin D and its association with disease characteristics in germ cell tumours - Lesko, Peter; Vlkova, Barbora; Kalavska, Katarina; De Angelis, Valentina; Novotna, Vera; Obertova, Jana; Orszaghova, Zuzana; Palacka, Patrik; Rejlekova, Katarina; Sycova-Mila, Zuzana; Kollarik, Boris; Aziri, Ramadan; et al. (Frontiers in Oncology, 2023)
Background: Testicular cancer is the most common malignancy among young men. Vitamin D has pluripotent effects on cancer pathogenesis and plays a role in the metastatic cascade. The aim of this study is to analyze plasma vitamin D in association with clinico-pathological findings and prognosis in patients with germ-cell tumours (GCTs). Methods: This study included 120 newly diagnosed and/or relapsed GCTs patients treated from April 2013 to July 2020 for whom plasma was available in the biobank. Blood samples were drawn at the time before 1st chemotherapy cycle as well as before the 2nd cycle. Plasma vitamin D was measured using ELISA and correlated with disease characteristics and the outcome. For survival analysis the cohort was dichotomized to “low” and “high” based on median vitamin D. Results: There was no significant difference in vitamin D plasma level between healthy donors and GCT patients, p = 0.71. Vitamin D level was not associated with disease characteristics except of brain metastases, where patients with brain metastases had D vitamin level of 32% lower compared to patients without brain metastases, p=0.03. Vitamin D was also associated with response to chemotherapy, with an approximately of 32% lower value in patients with unfavorable response compare to favorable response, p=0.02. Moreover, low plasma D vitamin was significantly associated with disease recurrence and inferior progression-free survival (PFS) but not with overall survival (OS) (HR= 3.02, 95%CI 1.36-6.71, p = 0.01 for PFS and HR= 2.06, 95%CI 0.84 – 5.06, p = 0.14 for OS, respectively). Conclusion: Our study suggests a prognostic value of pretreatment vitamin D concentrations in GCTs patients. Low plasma vitamin D was associated with unfavorable response to therapy and disease recurrence. However, it remains to elucidate whether the biology of the disease confirms a causative role of low vitamin D and if its supplementation affects the outcome.